2019
DOI: 10.1186/s12882-019-1314-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in patients with atypical hemolytic uremic syndrome treated with eculizumab in a long-term observational study

Abstract: Background There are limited long-term outcome data in eculizumab-treated patients with atypical hemolytic uremic syndrome (aHUS). We report final results from the largest prospective, observational, multicenter study of patients with aHUS treated with eculizumab. Methods Patients with aHUS who participated in any of five parent eculizumab trials and received at least one eculizumab infusion were eligible for enrollment in a long-term follow-up study. Rates of thromboti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 22 publications
4
81
2
6
Order By: Relevance
“…The complement protein C5 inhibitor eculizumab (Soliris®, Alexion Pharmaceuticals, Inc., Boston, MA, United States) has been shown to be efficacious and safe in treating aHUS in adults and children over the last decade, both in clinical trials and real-world settings [6][7][8][9][10][11][12][13]. However, despite its proven effectiveness, intravenous (IV) eculizumab infusions are required once every 2 weeks, which may be burdensome for patients and caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…The complement protein C5 inhibitor eculizumab (Soliris®, Alexion Pharmaceuticals, Inc., Boston, MA, United States) has been shown to be efficacious and safe in treating aHUS in adults and children over the last decade, both in clinical trials and real-world settings [6][7][8][9][10][11][12][13]. However, despite its proven effectiveness, intravenous (IV) eculizumab infusions are required once every 2 weeks, which may be burdensome for patients and caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…But plasma therapy was not effective; historically, aHUS had a poor prognosis with significant morbidity and mortality, with up to 50% of pa www.chikd.org tients progressing to endstage renal disease (ESRD), and 10 to 15% mortality rate during the acute phase. Treatment with eculizumab was proven to be effective in aHUS, sub stantially improving patient survival and preventing prog ression to ESRD and disease recurrence 6,9,10) . Eculizumab in aHUS led to hematological normalization and reduced renal injury with significantly improved kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…The use of eculizumab as a preemptive strategy in KT candidates with known aHUS is ongoing. Several studies have reported the clinical outcomes of KT recipients with ec-ulizumab prophylaxis [89][90][91]. The results showed that eculizumab prophylaxis at the time of KT markedly reduced the incidence of recurrent TMA events, compared to data from the era before eculizumab [28,86].…”
Section: Kidney Transplantationmentioning
confidence: 99%